The essence of the concept of "innovative technology" in the teaching of economic disciplines - Pogorelova, T. A.; Pererva, P. G. (ФОП Панов А. М., 2023)
It is proven that innovations are fully included in the concept of modernization or modernization of educational and educational work. Innovations in education can be a method, methodology, pedagogical tool, program, technology, etc. Innovation is often understood as a certain process, a purposeful progressive change. Less often, innovation is the very means by which the system begins to change.
Сутність поняття "інноваційна технологія" у викладанні економічних дисциплін
Keywords: training; innovative technologies; teaching; economic disciplines; quality